Composite binder for improving safety of positive electrode as well as preparation method and application of composite binder
By using composite binder in the positive electrode of lithium-ion battery, combining phosphorenol pyruvate derivatives and fluoropolymers, the short circuit problem when lithium-ion battery thermal runaway is solved and the safety of the battery is improved.
Patent Information
- Application Number
- CN202411751982.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-04-11
AI Technical Summary
Lithium-ion batteries are prone to short circuits inside the battery when thermally out of control, resulting in a sharp increase in temperature and poses safety hazards.
A composite binder is used, which is made of a phosphorenol pyruvate derivative and an acrylate monomer polymer, and combines a fluorine-containing polymer to form a polymer binder to improve the safety of the positive electrode.
While ensuring the electrochemical performance of the battery, it effectively reduces the risk of short-circuit when the lithium-ion battery is thermally out of control, reduces the possibility of a sharp increase in temperature, and improves the safety of the positive electrode.
Smart Images

Figure BDA0005165222520000021 
Figure BDA0005165222520000061 
Figure BDA0005165222520000071
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field related to batteries, and in particular relates to a composite binder for improving the safety of a positive electrode, and a preparation method and application thereof. Background Art
[0002] Since the commercialization of lithium-ion batteries in the late 20th century, lithium-ion batteries have become one of the most excellent battery systems with comprehensive performance due to their advantages such as lightweight, high operating voltage, excellent cycle life and outstanding energy density. They have been widely used in many fields such as consumer electronics, energy storage power stations and power vehicles. Common lithium-ion battery cathode materials include lithium cobalt oxide, lithium iron phosphate, ternary materials and lithium manganese oxide. Among them, ternary cathode materials have become the two mainstream power battery cathode materials together with lithium iron phosphate due to their excellent reversible cycle specific capacity and high energy density. However, the thermal runaway problem of lithium-ion batteries that occurs from time to time poses a challenge to their safe application. The main causes of thermal runaway include battery deformation caused by needle puncture and extrusion; melting and decomposition of the internal diaphragm of the battery cell caused by external overheating environment; and overcharging, over-discharging and other abuse conditions that induce dendrites inside the battery and pierce the diaphragm. Therefore, how to effectively reduce the risk of thermal runaway of lithium-ion batteries has become an important issue that needs to be solved urgently.
[0003] At present, the commonly used binder in the preparation of positive electrode plates is polyvinyl fluoride polymer, which often only plays the role of bonding the materials in the plate, and is of little help in reducing the thermal runaway of lithium-ion batteries. Therefore, it is urgent to develop a binder that can improve the safety of the positive electrode to improve the problem of a sharp increase in temperature caused by internal short circuits in lithium-ion batteries when thermal runaway occurs. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a composite binder for improving the safety of the positive electrode and its preparation method and application, which effectively improves the technical problem of a sharp increase in temperature caused by an internal short circuit of the battery when thermal runaway occurs in the lithium-ion battery while ensuring the electrochemical performance of the battery, thereby improving the safety of the positive electrode.
[0005] To solve the above technical problems, the first aspect of the present invention provides a composite adhesive, including a first adhesive and a second adhesive, wherein the first adhesive is polymerized from phosphoenolpyruvic acid derivatives and acrylate monomers, and the second adhesive is a fluorine-containing polymer.
[0006] Specifically, the composite adhesive of the present invention comprises a first binder polymerized from a phosphoenolpyruvic acid derivative and an acrylate monomer and a conventional fluorine-containing polymer (second binder), and the two binders work together to improve the safety of the positive electrode while ensuring the electrochemical performance of the battery. Among them: the structure of the phosphoenolpyruvic acid derivative contains phosphoenolpyruvic acid, and its structural formula is shown in formula (1).
[0007]
[0008] The structure contains double bonds, which can be polymerized with other double bond monomers (such as acrylate monomers) to form a polymer binder. At the same time, the structure also contains phosphoric acid and carboxylic acid groups, which can react with alkali to form corresponding phosphates and carboxylates to improve the safety of the positive electrode. The reasons are as follows: First, phosphates such as magnesium phosphate and calcium phosphate have certain flame retardancy, and produce a structurally stable carbonized layer during thermal runaway, which prevents further thermal decomposition of the positive electrode material and blocks the oxygen released from the positive electrode from further reacting with the electrolyte or the negative electrode. Second, such as magnesium phosphate groups, the groups decompose after heating, and the bonding force of the binder decreases. At this time, microcracks will appear on the surface of the positive electrode plate, and the internal resistance of the plate will increase, so that the short-circuit current will decrease when the battery is in thermal runaway, thereby reducing the heat generation of the battery. Third, the carboxylic acid and phosphoric acid groups that have not reacted with alkali will react with the residual alkali on the surface of the high-nickel positive electrode active material inside the positive electrode, reducing the amount of residual alkali on the surface of the positive electrode particles, thereby reducing the gas production of the positive electrode during thermal runaway.
[0009] In some embodiments of the present invention, the phosphoenolpyruvate derivative is selected from at least one of phosphoenolpyruvate, phosphoenolpyruvate lithium salt, phosphoenolpyruvate sodium salt, phosphoenolpyruvate calcium salt, phosphoenolpyruvate magnesium salt, phosphoenolpyruvate aluminum salt, phosphoenolpyruvate cyclohexylammonium salt, and phosphoenolpyruvate tricyclohexylammonium salt.
[0010] In some embodiments of the present invention, the acrylic acid ester monomer is selected from at least one of methyl acrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, and isopropyl methacrylate.
[0011] In some embodiments of the present invention, the fluorine-containing polymer is selected from at least one of polyvinylidene fluoride, polychlorotrifluoroethylene, polytrifluoroethylene, poly(ethylene-tetrafluoroethylene) copolymer, poly(ethylene-chlorotrifluoroethylene), polyvinyl fluoride, and poly(vinylidene fluoride-trifluoroethylene).
[0012] In some embodiments of the present invention, the mass ratio of the first binder to the second binder is (1-2):1, such as 1:1, 1.5:1 or 2:1, including but not limited to the listed values; at the same time, other values not listed within the numerical range are also applicable.
[0013] In some embodiments of the present invention, the content of the phosphoenolpyruvic acid derivative in the first binder is 30-80 wt %; preferably, the content of the phosphoenolpyruvic acid derivative in the first binder is 40-70 wt %.
[0014] In some embodiments of the present invention, the polymerization method of the first binder includes any one of solution polymerization, suspension polymerization, bulk polymerization, and emulsion polymerization. In addition, as the polymerization reaction, any one of ionic polymerization, free radical polymerization, and living free radical polymerization can be used. Moreover, the emulsifier, dispersant, polymerization initiator, chain transfer agent, etc. used in the polymerization reaction can also use conventional reagents.
[0015] In some embodiments of the present invention, the steps of preparing the first binder by solution polymerization are as follows:
[0016] (1) dissolving an acrylic acid ester monomer and an initiator in an organic solvent to obtain a mixed solution;
[0017] (2) dropping the mixed solution into a solution of a phosphoenolpyruvic acid derivative to perform a polymerization reaction under an inert atmosphere; then rotary evaporating the reaction product to remove the organic solvent; then adding methanol to dissolve and wash away unreacted acrylate monomers; and finally drying to obtain the first binder powder.
[0018] In some embodiments of the present invention, the organic solvent may be an organic solvent commonly used in the art, such as tetrahydrofuran (THF).
[0019] In some embodiments of the present invention, the amount of the organic solvent used is 1.5-2.5 times the total weight of the acrylic ester monomers.
[0020] In some embodiments of the present invention, the initiator may be selected from initiators commonly used in the art, such as azobisisobutyronitrile (AIBN).
[0021] In some embodiments of the present invention, the amount of the initiator is 0.5-1 wt % of the total weight of the acrylic ester monomers.
[0022] In some embodiments of the present invention, the temperature of the hydrothermal reaction is 70-90°C.
[0023] In some embodiments of the present invention, the hydrothermal reaction time is 3-5 hours.
[0024] In some embodiments of the present invention, the mixed solution is added dropwise for 2-4 hours.
[0025] In some embodiments of the present invention, the rotary evaporation is carried out under the conditions of vacuum degree ≤ 0.095 MPa and temperature of 70-90°C.
[0026] In some embodiments of the present invention, the drying is carried out under vacuum conditions at a temperature of 70-90° C. for 10-15 hours.
[0027] The second aspect of the present invention provides a method for preparing the composite adhesive according to the first aspect, comprising the following steps:
[0028] The first binder and the second binder are dissolved in an organic solvent and mixed to obtain the composite binder.
[0029] In some embodiments of the present invention, the solid content of the composite binder is 4-8 wt %.
[0030] In some embodiments of the present invention, the organic solvent may be an organic solvent commonly used in the art, such as N-methylpyrrolidone (NMP).
[0031] The third aspect of the present invention provides a positive electrode plate, including a positive electrode current collector and a positive electrode active material layer arranged on the surface of the positive electrode current collector, and the raw materials for preparing the positive electrode active material layer include the composite binder described in the first aspect, or include the composite binder prepared by the preparation method described in the second aspect.
[0032] In some embodiments of the present invention, the raw materials for preparing the positive electrode active material layer further include a positive electrode active material and a positive electrode conductive agent.
[0033] In some embodiments of the present invention, the positive electrode active material is selected from at least one of nickel-cobalt-manganese ternary materials, nickel-cobalt-aluminum ternary materials, lithium cobalt oxide, lithium iron phosphate, and lithium-rich manganese-based materials.
[0034] In some embodiments of the present invention, the positive electrode active material is selected from LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.33 Co 0.33 Mn 0.33 O2(NCM111), LiNi 0.8 Co 0.15 Al 0.05 At least one of O2(NCA).
[0035] In some embodiments of the present invention, the particle size of the positive electrode active material is 2-15 μm.
[0036] In some embodiments of the present invention, the positive electrode conductive agent is selected from at least one of carbon nanotubes, graphene, carbon black, and carbon fibers.
[0037] In some embodiments of the present invention, in the raw materials for preparing the positive electrode active material layer, the mass ratio of the positive electrode active material, the composite binder and the positive electrode conductive agent is (93-98): (1-3): (1-4), such as 97:1:2, 93:3:4, 95:2:3, 98:1:1, etc., including but not limited to the listed values; at the same time, other values not listed within the numerical range are also applicable.
[0038] In some embodiments of the present invention, the raw material for preparing the positive electrode active material layer further includes an organic solvent, such as NMP.
[0039] A fourth aspect of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet described in the third aspect.
[0040] In some embodiments of the present invention, the lithium-ion battery further comprises a negative electrode plate, the raw materials for preparing the negative electrode plate comprise a negative electrode current collector and a negative electrode active material layer disposed on the surface of the negative electrode current collector, and the raw materials for preparing the negative electrode active material layer comprise a negative electrode active material, a negative electrode conductive agent and a binder.
[0041] In some embodiments of the present invention, the negative electrode active material may be a negative electrode active material commonly used in the art, such as graphite.
[0042] In some embodiments of the present invention, the negative electrode conductive agent is selected from at least one of carbon nanotubes, graphene, carbon black, and carbon fibers.
[0043] In some embodiments of the present invention, the binder is selected from at least one of polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), polyacrylic acid (PAA), lithium polyacrylate (PAALi), and sodium carboxymethyl cellulose (CMC).
[0044] In some embodiments of the present invention, in the raw materials for preparing the negative electrode active material layer, the mass ratio of the negative electrode active material, the binder and the negative electrode conductive agent is (94-98):(1-3):(1-3), such as 96:2:2, 94:3:3, 97:1:2, 98:1:1, etc., including but not limited to the listed values; at the same time, other values not listed within the numerical range are also applicable.
[0045] In some embodiments of the present invention, the lithium-ion battery further comprises a separator and an electrolyte.
[0046] In some embodiments of the present invention, the separator is selected from polyolefin separators, such as at least one of polyethylene (PE), polypropylene (PP), and PP / PE / PP.
[0047] In some embodiments of the present invention, the electrolyte contains a lithium salt and a solvent.
[0048] In some embodiments of the present invention, the lithium salt is selected from at least one of LiPF6, LiBF4, and LiTFSI, and may be any conventional lithium salt without particular limitation.
[0049] In some embodiments of the present invention, the solvent is a mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC).
[0050] In some embodiments of the present invention, the volume ratio of EC, EMC and DEC in the solvent is (0.5-2):(0.5-2):1.
[0051] In some embodiments of the present invention, the volume ratio of EC, EMC and DEC in the solvent is (0.5-1.5):(0.5-1.5):1.
[0052] In some embodiments of the present invention, the volume ratio of EC, EMC and DEC in the solvent is 1:1:1.
[0053] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:
[0054] The composite binder of the present invention includes a first binder polymerized from phosphoenolpyruvic acid derivatives and acrylate monomers and a second binder containing fluorine polymers. The two binders work together to improve the safety of the positive electrode while ensuring the electrochemical performance of the battery. Among them: the structure of the phosphoenolpyruvic acid derivatives contains phosphoric acid and carboxylic acid groups, which can react with alkali to form corresponding phosphates and carboxylates, effectively improving the rapid increase in temperature caused by internal short circuits in the battery when thermal runaway occurs in the lithium-ion battery, thereby improving the safety of the positive electrode. The adhesion of the fluorine-containing polymer is stronger than that of the first binder, which ensures the overall bonding effect of the positive electrode sheet, thereby ensuring the first coulomb efficiency and cycle retention rate of the battery. DETAILED DESCRIPTION
[0055] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.
[0056] Example 1
[0057] A composite binder includes a first binder and a second binder, wherein the first binder is polymerized from lithium phosphoenolpyruvate and methyl methacrylate, and the second binder is polyvinylidene fluoride. The preparation method of the composite binder includes the following steps:
[0058] (1) Preparation of the first binder by solution polymerization: A four-necked flask equipped with a constant pressure dropping funnel, a serpentine condenser, a thermometer and a mechanical stirring device was placed in a constant temperature water bath at 80°C, and the reaction device was evacuated and operated with Ar. After three cycles, a THF solution of methyl methacrylate (MMA) and azobisisobutyronitrile initiator (AIBN, added in an amount of 1 wt% of the total weight of MMA) (added in an amount of 200 wt% of the total weight of MMA) was uniformly dripped into a THF solution of lithium phosphoenolpyruvate (MMA and AIBN) pre-filled with the mixture. The mass ratio of lithium phosphoenolpyruvate is 45:55), and a hydrothermal reaction is carried out, the dropping time is controlled to be 3 hours, and the insulation time is 4 hours; after the reaction is completed, the liquid in the four-necked flask is poured into a single-necked flask, and rotary evaporation is carried out at 80°C, and the vacuum degree is ≤0.095MPa; after removing most of the THF, excess methanol is added to the flask to dissolve and wash away the unreacted monomers, and after repeating 3 times, the obtained product block is placed in a vacuum oven at 80°C and dried for 12 hours; finally, the product block is crushed to obtain the first binder powder.
[0059] (2) The first binder and the second binder prepared in step (1) are dissolved in NMP at a mass ratio of 6:4 to obtain a composite binder with a solid content of 6 wt %.
[0060] A positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the surface of the positive electrode current collector. The preparation method of the positive electrode sheet includes the following steps:
[0061] The positive electrode active material NCM811 (particle size of 2-15 μm), the conductive agent carbon nanotubes, and the composite binder prepared in this embodiment were mixed in a mass ratio of 97:1:2, and the solvent NMP was added. The mixture was stirred evenly to obtain a positive electrode slurry; then the positive electrode slurry was evenly coated on both sides of the positive electrode current collector aluminum foil, and vacuum dried at 80°C for 24 hours to obtain a positive electrode sheet with a surface capacity of 3.0 mAh / cm 2 .
[0062] Examples 2-8 and Comparative Examples 1-4
[0063] The preparation methods of the composite binders and positive electrode sheets of Examples 2-8 and Comparative Examples 1-4 are the same as those of Example 1, except that: the selection of raw materials for the preparation of the positive electrode active material and the first binder, the dosage relationship of the raw materials for the preparation of the first binder, and the mass ratio of the first binder to the second binder are different, as shown in Table 1.
[0064] Table 1:
[0065]
[0066]
[0067] Application Examples
[0068] The positive electrode sheets prepared in the above-mentioned Examples 1-8 and Comparative Examples 1-4 are respectively used to make lithium-ion batteries, and the specific steps are as follows:
[0069] (1) Preparation of negative electrode sheet
[0070] The negative electrode active material graphite, conductive agent carbon nanotubes, binder CMC and SBR were mixed in a mass ratio of 96:1:1.5:1.5, water was added, and the mixture was stirred evenly to obtain a negative electrode slurry; then the negative electrode slurry was evenly coated on both sides of the negative electrode current collector copper foil, and vacuum dried at 80°C for 24 hours to obtain a negative electrode sheet with a surface capacity of 3.3 mAh / cm 2 .
[0071] (2) Preparation of electrolyte
[0072] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed at a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent at a concentration of 1 mol / L to obtain an electrolyte after full dissolution.
[0073] (3) Preparation of isolation membrane
[0074] A polyethylene film was selected as the separator.
[0075] (4) Preparation of lithium-ion batteries
[0076] After the positive and negative electrode sheets are rolled and die-cut, they are placed in an automatic stacking machine for assembly with the diaphragm. After the tabs are welded, they are placed in the punched aluminum-plastic film and heat-sealed. Then, the electrolyte is added to the aluminum-plastic film in an environment with a dew point of -60°C and packaged. After activation at a current of 0.1C, the airbag is cut off and packaged again to obtain a lithium-ion battery.
[0077] Performance Testing
[0078] The lithium-ion battery prepared in the above application example was tested for thermal abuse, initial coulombic efficiency and cycle performance. The test method is as follows:
[0079] First coulombic efficiency: At room temperature, the lithium-ion battery is charged and discharged at a rate of 0.1C. The first coulombic efficiency = first discharge capacity / first charge capacity × 100%;
[0080] Cycle performance: At room temperature, the lithium-ion battery is cycled at 0.1C. When the discharge capacity is less than 80% of the initial discharge capacity, the battery reaches the end of life.
[0081] Thermal abuse test: The battery is stored at 180°C for 1 hour to check whether the battery will catch fire or explode. Samples that pass the hot box test are marked as "√", and samples that catch fire or explode are marked as "×".
[0082] The test results are shown in Table 2.
[0083] Table 2:
[0084] First coulombic efficiency (%) 0.1C cycle 100 times, capacity retention rate (%) Thermal Abuse Test Results Example 1 92.4 98.9 √ Example 2 92.8 99.1 √ Example 3 92.3 98.5 √ Example 4 92.4 99.2 √ Example 5 93.0 99.4 √ Example 6 93.1 99.0 √ Example 7 93.2 98.7 √ Example 8 92.8 98.5 √ Comparative Example 1 92.3 99.1 × Comparative Example 2 83.2 75.6 √ Comparative Example 3 93.5 98.9 × Comparative Example 4 65.3 33.2 √
[0085] It can be seen from Table 1-2 that the lithium-ion batteries assembled with the positive electrode sheets prepared by the composite binders of Examples 1-8 all have good first coulombic efficiency and cycle capacity retention rate, and all pass the thermal abuse test, indicating that the risk of the battery catching fire or exploding at high temperature is relatively small.
[0086] The positive electrode active materials of Examples 1-4 are the same, and the difference is that different phosphoenolpyruvic acid derivatives are used to prepare the first binder, which shows that the phosphoenolpyruvic acid derivatives are applicable and effective to the present invention.
[0087] The composite binders of Examples 5-6 are the same, the difference being that different positive electrode active materials are used, which indicates that the composite binder of the present invention is universal for high-nickel ternary positive electrode materials.
[0088] The positive electrode active materials and phosphoenolpyruvic acid derivatives of Examples 7-8 are the same, except that different acrylate monomers are used to prepare the first binder, which indicates that acrylate monomers are applicable and effective to the present invention.
[0089] The differences between Comparative Examples 1-4 and Example 1 are as follows: the first binder of Comparative Example 1 does not contain lithium phosphoenolpyruvate, the first binder of Comparative Example 2 does not contain methyl methacrylate, Comparative Example 3 uses a single second binder, polyvinylidene fluoride, and Comparative Example 4 uses a single first binder.
[0090] The results show that the binders of Comparative Examples 1 and 3 do not contain phosphoenolpyruvic acid derivatives, and therefore fail the thermal abuse test.
[0091] The binder of Comparative Example 2 does not contain an acrylic ester monomer, and the bonding performance of the entire positive electrode plate is poor. Therefore, the first coulombic efficiency and cycle capacity retention rate of the battery are not good.
[0092] Since the binder of Comparative Example 4 does not contain the second binder polyvinylidene fluoride, and the bonding performance of the second binder is better than that of the first binder, the overall bonding effect of the positive electrode plate is very poor, and the first coulombic efficiency and cycle capacity retention rate of the battery are also greatly reduced.
[0093] In summary, the present invention can effectively improve the safety of lithium-ion batteries and reduce the risk of thermal runaway of batteries while ensuring the electrochemical performance of lithium-ion batteries by introducing phosphorenolpyruvic acid polymers into conventional fluorine-containing polymer binders.
[0094] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.
Claims
1. A composite adhesive, characterized in that: The invention comprises a first binder and a second binder, wherein the first binder is formed by polymerizing a phosphorenolpyruvic acid derivative and an acrylate monomer, and the second binder is a fluorine-containing polymer.
2. The composite adhesive according to claim 1, characterized in that: The phosphoenolpyruvate derivative is selected from at least one of phosphoenolpyruvate, phosphoenolpyruvate lithium salt, phosphoenolpyruvate sodium salt, phosphoenolpyruvate calcium salt, phosphoenolpyruvate magnesium salt, phosphoenolpyruvate aluminum salt, phosphoenolpyruvate cyclohexylammonium salt, and phosphoenolpyruvate tricyclohexylammonium salt; And / or, the acrylic acid ester monomer is at least one selected from methyl acrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, and isopropyl methacrylate; And / or, the fluorine-containing polymer is at least one selected from polyvinylidene fluoride, polychlorotrifluoroethylene, polytrifluoroethylene, poly(ethylene-tetrafluoroethylene) copolymer, poly(ethylene-chlorotrifluoroethylene), polyvinyl fluoride, and poly(vinylidene fluoride-trifluoroethylene).
3. The composite adhesive according to claim 1 or 2, characterized in that: The mass ratio of the first binder to the second binder is (1-2):
1.
4. The composite adhesive according to claim 1 or 2, characterized in that: In the first binder, the content of the phosphoenolpyruvic acid derivative is 30-80 wt %.
5. The composite adhesive according to claim 1, characterized in that: The polymerization method of the first binder includes any one of solution polymerization, suspension polymerization, bulk polymerization and emulsion polymerization.
6. A method for preparing a composite adhesive according to any one of claims 1 to 5, characterized in that: The following steps are involved: The first binder and the second binder are dissolved in an organic solvent and mixed to obtain the composite binder.
7. The method for preparing the composite adhesive according to claim 6, characterized in that: The solid content of the composite binder is 4-8wt%.
8. A positive electrode sheet, characterized in that: It comprises a positive electrode current collector and a positive electrode active material layer arranged on the surface of the positive electrode current collector, wherein the raw material for preparing the positive electrode active material layer comprises the composite binder as described in any one of claims 1 to 5, or comprises the composite binder prepared by the preparation method as described in claim 6 or 7.
9. The positive electrode sheet according to claim 8, characterized in that: The raw materials for preparing the positive electrode active material layer also include positive electrode active materials and conductive agents; the positive electrode active material is selected from at least one of nickel-cobalt-manganese ternary materials, nickel-cobalt-aluminum ternary materials, lithium cobalt oxide, lithium iron phosphate, and lithium-rich manganese-based materials; the conductive agent is selected from at least one of carbon nanotubes, graphene, carbon black, and carbon fibers.
10. A lithium ion battery, characterized in that: Comprising the positive electrode sheet as described in claim 8 or 9.